THE CORRELATION BETWEEN STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION AND WRITING SKILL - Irham Miftakhul Jannah; Sherly Citra Putri; Siti Masrifah (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2021)
The objective of the research was to investigate the correlation between student’s achievement in reading comprehension and writing skill, whether there was any correlation between student’s achievement in reading comprehension and writing skill. The population of this research was 283 students. The researchers took 30 % as the sample so there were 85 students as main subject of research. In this quantitative research, the researcher used correlation study by using Pearson Product Moment to calculate the data. There were two main variables in this research. Reading comprehension (variable X) and writing skill (variable Y). The instruments of this research were reading comprehension test and writing test. The data were collected through test (reading comprehension and writing test). From the calculation by using Pearson Product Moment formula, it was obtained that the value of “r” product moment (rxy) or “r” observation (r0) was 0,436. The degree of freedom (df) was 83. The degree of significance 5% was 0,213, and the degree of significance 1% was 0,278. So, it meant that the hypothesis r0 was bigger than rt (0,436>0,0,213 and 0,436<0,278). The result of hypothesis of this research was alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. It meant there was correlation between student’s achievement in reading comprehension and writing skill.